Effect of pesticides 2, 4-on hematological parameters of channa punctatus - Kumar, Pravesh; Kumar Gupta, Yogesh; Pandey, Devendra (International Journal of Biological Research, 2016)
Pesticides are chemicals used for pest control in the agricultural fields. Modern agricultural pesticides result in indiscriminate use of various pesticides. Which usually enter into the aquatic environment? They finally reach the surrounding water bodies through surface runoff affecting the aquatic fauna. 2, 4-D is frequently used pesticides due to its effectiveness and rapid breakdown into environmentally safe products. A 96hr static sub-lethal concentration toxicity test was carried out to determine the LC50 value of 2, 4-D on the snake head fish channa punctatus. The fish were exposed to 5 different concentrations of 2, 4-D (40, 45, 50, 55 & 60ppm) for toxicity. Control (0.0ppm) was also carried out. The data were subjected to Finney’s Probit analysis and processed with Trimmed Spearman-Karber statistical software. The LC50 values for 2, 4-D for 24, 48, 72 and 96hr were 4.87, 3.12, 2.69 and 1.92 mgl-1 respectively. At higher concentration of 2, 4-D (3.25 mgl-1 and above) the fish showed uncoordinated behavior such as erratic and jerky swimming, attempt to jump out of water, frequent surfacing and effected the allover of body.